Channel observation‐based scaled backoff mechanism for high‐efficiency WLANs. Issue 10 (1st May 2018) - Ali, R.; Shahin, N.; Kim, Y.‐T.; Kim, B.‐S.; Kim, S.W.
Abstract : A channel observation‐based scaled backoff (COSB) mechanism for the carrier sense multiple access with collision avoidance of high efficiency wireless local area networks (WLANs) is devised. The proposed protocol modifies the blind scaling of contention window ( W ) in binary exponential backoff (BEB) scheme of currently deployed WLANs. COSB is employed to adaptively scale‐up and scale‐down the W size during the backoff mechanism for collided and successfully transmitted data frames, respectively. It can achieve higher throughput and shorter delay compared to the conventional BEB mechanism in highly dense WLANs.